2023
DOI: 10.3390/ijms24021138
|View full text |Cite
|
Sign up to set email alerts
|

Zymosan Particle-Induced Hemodynamic, Cytokine and Blood Cell Changes in Pigs: An Innate Immune Stimulation Model with Relevance to Cytokine Storm Syndrome and Severe COVID-19

Abstract: Hemodynamic disturbance, a rise in neutrophil-to-lymphocyte ratio (NLR) and release of inflammatory cytokines into blood, is a bad prognostic indicator in severe COVID-19 and other diseases involving cytokine storm syndrome (CSS). The purpose of this study was to explore if zymosan, a known stimulator of the innate immune system, could reproduce these changes in pigs. Pigs were instrumented for hemodynamic analysis and, after i.v. administration of zymosan, serial blood samples were taken to measure blood cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 94 publications
(113 reference statements)
1
3
0
Order By: Relevance
“…In theory, Comirnaty-indued C activation can enhance cytokine release via anaphylatoxin receptors and via opsonization of nanoparticles, thus enhancing their uptake and binding to inflammation-signaling pattern (and/or danger) receptors of immune cells. In support of the latter possibility, previous studies from our laboratory showed temporal correlation between C activation and release of inflammatory cytokines by zymosan in pigs 79 , and suppression of zymosan-induced IL-6 release in PBMC culture by factor H, an inhibitor of altrnative pathway C activation 46 . As for the observation that heat-treatment of serum suppressed the production of IL-1α, IL-1β and TNFα, the phenomenon is most likely due to inactivation of (a) heat labile C protein(s) that play (a) causal role(s) in the secretion of the above and possibly other cytokines.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…In theory, Comirnaty-indued C activation can enhance cytokine release via anaphylatoxin receptors and via opsonization of nanoparticles, thus enhancing their uptake and binding to inflammation-signaling pattern (and/or danger) receptors of immune cells. In support of the latter possibility, previous studies from our laboratory showed temporal correlation between C activation and release of inflammatory cytokines by zymosan in pigs 79 , and suppression of zymosan-induced IL-6 release in PBMC culture by factor H, an inhibitor of altrnative pathway C activation 46 . As for the observation that heat-treatment of serum suppressed the production of IL-1α, IL-1β and TNFα, the phenomenon is most likely due to inactivation of (a) heat labile C protein(s) that play (a) causal role(s) in the secretion of the above and possibly other cytokines.…”
Section: Discussionsupporting
confidence: 63%
“…Doxebo was used as control for Comirnaty because of the similaries of their nanostuctures 62 and wealth of information on C-activation and related hypersensitivity/anaphylactoid reactions caused by Doxebo' parent drug, Doxil 44,[76][77][78] . Finally, zymosan, the gold standard of C activation was used as positive control, as in all our previous in vitro 17,46 and in vivo 17,79,80 studies on CARPA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The other Comirnaty-induced proinflammatory process analyzed in the present study as a possible contributing mechanism to the vaccine-induced SAEs was the induction of inflammatory cytokines and its dependence on C activation. A crosstalk between these two arms of the innate immune system has already been described in many previous studies [55,[67][68][69][70], but not for mRNA-LNP vaccine-induced immune stimulation. In theory, Comirnaty can enhance cytokine release both via direct interaction with immune cells and their indirect stimulation via anaphylatoxin and other C receptors, and our PBMC data (Figure 6) gave an indication of the operation of both mechanisms.…”
Section: Inflammatory Cytokine Production By Comirnaty: Mechanism And...mentioning
confidence: 71%